2020
DOI: 10.3389/fspor.2020.568420
|View full text |Cite
|
Sign up to set email alerts
|

The Acute and Longer-Term Effects of Cold Water Immersion in Highly-Trained Volleyball Athletes During an Intense Training Block

Abstract: Background: The use of cold water immersion (CWI) as a recovery strategy following exercise has drawn mixed findings over the last few decades. The purpose of the current study was twofold ; (1) to determine the acute effects of CWI within the training week, and (2) to investigate the longer-term effects of CWI over a 16-day period. Methods: In a randomized, controlled trial, 13 national-level volleyball athletes were allocated to two groups, an experimental (CWI, n = 7) and a control group (n = 6) during a 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(57 reference statements)
0
3
1
Order By: Relevance
“…An alternative explanation is that postexercise water immersion results in temperature-dependent changes in power production by an elevated rate of anaerobic metabolism (15) and creates a favorable hormonal environment to aid the recovery of neuromuscular performance (9), with both aspects confirmed by our results (Figures 3 and 5). The outcomes of this study differ to other research reporting postexercise CWI did not influence acute neuromuscular performance in volleyball (9,52), or weightlifting (47) athletes, nor in recreational subjects after resistance exercise (2). However, the study in weightlifters (47) demonstrated intersubject differences with some improvements in neuromuscular performance obtained on an individual basis, while we report a high variability in individual response as evident by the SD in Figures 2–4 (above).…”
Section: Discussioncontrasting
confidence: 99%
“…An alternative explanation is that postexercise water immersion results in temperature-dependent changes in power production by an elevated rate of anaerobic metabolism (15) and creates a favorable hormonal environment to aid the recovery of neuromuscular performance (9), with both aspects confirmed by our results (Figures 3 and 5). The outcomes of this study differ to other research reporting postexercise CWI did not influence acute neuromuscular performance in volleyball (9,52), or weightlifting (47) athletes, nor in recreational subjects after resistance exercise (2). However, the study in weightlifters (47) demonstrated intersubject differences with some improvements in neuromuscular performance obtained on an individual basis, while we report a high variability in individual response as evident by the SD in Figures 2–4 (above).…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, CWI does not seem to promote detrimental effects on performance in the subsequent day of its application for soccer and volleyball athletes. 69,70 However, the technique may attenuate performance immediately after its application. 56,71 Thus, because of the current controversial state of the art on this matter, care must be taken when deciding whether or not to apply the CWI, especially regarding the desired objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work (Table 1) examining the longer-term effects of CWI on training performance and recovery amongst professional and semi-professional athletes provides invaluable insights regarding CWI programming and recovery-adaptation interaction throughout training/competition phases (Lindsay et al, 2016;Tavares et al, 2019Tavares et al, , 2020Seco-Calvo et al, 2020). These studies collectively demonstrate no impairments in strength gains despite administering frequent post-exercise CWI over 2.5 weeks to 8 months.…”
Section: Cwi and Resistance Training: Insights From Applied Researchmentioning
confidence: 98%